METHODS OF DEVELOPING A MOBILE APPLICATION FOR HEARING IMPAIRED CHILDREN - Salgarayeva, Г.И.; Makhanova, А.С. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2024)
The article explores the use of the cascade method to create a mobile application for hearing impaired children and the main stages of development. The process of developing special education in our society is carried out separately from general education organizations. This, in turn, has a significant impact on the transformation of methods and techniques used in teaching students with special educational needs, in particular children with hearing impairments. During the study, work was carried out to support and promote innovative technologies used by children with hearing impairments in order to improve the quality of their education, taking into account the peculiarities of learning in an inclusive environment. As a result of the research, an algorithm was proposed for the development of a educational mobile application aimed at allowing students with hearing impairments to fully integrate into the learning process. Convenient solutions were also proposed for determining the content of education, providing the content of the application used in teaching children with hearing impairments.